1998
DOI: 10.1523/jneurosci.18-08-02914.1998
|View full text |Cite
|
Sign up to set email alerts
|

A Ca2+-Independent Receptor for α-Latrotoxin, CIRL, Mediates Effects on Secretion via Multiple Mechanisms

Abstract: alpha-Latrotoxin (alpha-Ltx), a component of black widow spider venom, stimulates secretion from nerve terminals and from PC12 cells. In this study we examine the effects of expression of a newly cloned Ca2+-independent receptor for alpha-Ltx (CIRL) on secretion from bovine chromaffin cells. We first characterized the effect of alpha-Ltx on secretion from untransfected cells. alpha-Ltx, by binding in a Ca2+-independent manner to an endogenous receptor, causes subsequent Ca2+-dependent secretion from intact cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
0

Year Published

1998
1998
2004
2004

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(54 citation statements)
references
References 38 publications
3
51
0
Order By: Relevance
“…6D). In agreement with the previously published data (6,22), the bell-shaped secretion curve indicated that catecholamine release was mainly stimulated by Ca 2ϩ entry via toxin pores. Indeed, while exocytosis correlated with intracellular [Ca 2ϩ ] at lower [LTX WT ], excessive Ca 2ϩ influx induced by 3-5 nM LTX WT inhibited release as in Ref.…”
Section: Fig 2 Ltx N4c Is Unable To Form Ionic Pores a Influx Ofsupporting
confidence: 92%
See 1 more Smart Citation
“…6D). In agreement with the previously published data (6,22), the bell-shaped secretion curve indicated that catecholamine release was mainly stimulated by Ca 2ϩ entry via toxin pores. Indeed, while exocytosis correlated with intracellular [Ca 2ϩ ] at lower [LTX WT ], excessive Ca 2ϩ influx induced by 3-5 nM LTX WT inhibited release as in Ref.…”
Section: Fig 2 Ltx N4c Is Unable To Form Ionic Pores a Influx Ofsupporting
confidence: 92%
“…Secretion of Catecholamines from Bovine Chromaffin Cells-LTX is known to efficiently stimulate exocytosis of LDCV containing catecholamines and hormones in chromaffin and PC12 cells; this action is strictly Ca 2ϩ -dependent (6,36).…”
Section: Fig 2 Ltx N4c Is Unable To Form Ionic Pores a Influx Ofmentioning
confidence: 99%
“…Experimental (PTP , 1-875, or CIRL; 3 g/well) and control (pCMVneo; 3 g/well) plasmids were each mixed with pXGH5 (2 g/well) prior to generating the precipitates. Previous work in the laboratory has demonstrated that this ensures that Ͼ95% of transfected cells express both hGH and the protein of interest (36,37). hGH is stored in chromaffin granules and is released concomitantly with endogenous catecholamine by various secretagogues.…”
Section: Methodsmentioning
confidence: 99%
“…hGH was measured with a luminescent assay kit from Corning Nichols Institute Diagnostics (San Juan Capistrano, CA) (37). Endogenous catecholamines were measured by spectrofluorometric assay (40).…”
Section: Secretion Assaysmentioning
confidence: 99%
See 1 more Smart Citation